Reshaping imaginaries. Construction and reconstruction of city monuments between narration and experience - Leonzi, Silvia; Ciofalo, Giovanni; Ugolini, Lorenzo; Ciammella, Fabio; Quercia, Grazia (E|C, 2021)
The contribution aims to investigate the imaginary around the Spanish Steps monument of Rome through its audio visual representation. In the city context, the meanings attributed to places are recalled by multiple representations produced by media. Cultural products resemantize spaces, associating them with new social, cultural, and historical connotations (Ricci 2016). The study of the imaginary has, in fact, increased its centrality thanks to the multiplication of narratives, unveiling imaginal stratifications that result in a complex mediascape (Appadurai 2001). On the other hand, the evolving structures of the metropolis can be considered as media capable of generating experiences, meanings, stories that are reflected on screens. Based on these premises, we focused on the representation of the Spanish Steps through audio visual media (films, TV series and commercials) in order to understand the evolution of its imaginary.